2020
DOI: 10.1002/jts.22533
|View full text |Cite
|
Sign up to set email alerts
|

Metaphors For Trauma: A Cross‐Cultural Qualitative Comparison in Brazil, India, Poland, and Switzerland

Abstract: The concept of psychological trauma implies that people experiencing traumatic stress are wounded, thus relating to the metaphor of a physical injury. Although this notion is widely accepted by clinicians and researchers in mental health, there is evidence of a broad range of metaphorical idioms for extremely aversive experiences or catastrophic events across different cultures. In this ethnopsychological study, we aimed to investigate and contrast culturally shared metaphors for trauma among four distinct cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…In this process, several text passages were identified that did not permit a literal translation but required adaptation. Metaphors and idioms collected in the ethnopsychological study ( Shala et al, 2020 ) were used in such adaptations, inspired by research on metaphors and idioms of distress in cultural clinical psychology ( Rechsteiner et al, 2020 ). Translations were validated by consulting dictionaries, discussing essential idioms and metaphors in focus group discussions (FGDs), and gathering opinions of the Albanian-speaking team members.…”
Section: Methodsmentioning
confidence: 99%
“…In this process, several text passages were identified that did not permit a literal translation but required adaptation. Metaphors and idioms collected in the ethnopsychological study ( Shala et al, 2020 ) were used in such adaptations, inspired by research on metaphors and idioms of distress in cultural clinical psychology ( Rechsteiner et al, 2020 ). Translations were validated by consulting dictionaries, discussing essential idioms and metaphors in focus group discussions (FGDs), and gathering opinions of the Albanian-speaking team members.…”
Section: Methodsmentioning
confidence: 99%
“…Many reported of experiencing a ‘loss of orientation’, like the feeling of being in a ‘vacuum bubble’ or having an ‘empty picture’ in front of them after the natural disaster had hit them. The primary focus of this study was on adaptive responses to severe adversities; the adversities themselves (and related metaphors) are described elsewhere 59…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that alienation from psychological symptoms is more frequent in non-Western cultures 97. For the Pitaguary, this will be further investigated by focusing on adversity-related metaphors 59…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listening to these earthquake survivors' sorrowful narratives and exploring their everyday experiences in depth provide a key to understanding the cultural meaning of PTSD symptoms. It is pivotal for clinicians to listen to and understand victims' culturally specific metaphorical expressions of trauma as culture-specific expressions strongly reflect sociocultural and historical contexts and indicate potential approaches to the cultural adaptation of clinical interventions [39].…”
Section: Somatic Symptoms Tell a Story Of Deep Social Cultural And mentioning
confidence: 99%